Public Trust in The Management of Village Fund by Village Government - Kusumah Wardani, Ari; Risnawa, Wawan Risnawa; Juliarso, Ahmad; Kurniawan, Heri (Iapa Proceedings Conference, 2024)
This study aims to examine the Public Trust in Village Fund Management. The data collection techniques include observation, interviews and documentation. Data processing/analysis techniques in this study are reduction, display and verification. The decreasing public trust in the management of village funds by the village government is caused by the lack of transparency of the village government in the process of making village work programs, accountability for reporting village funds is not fully communicated to the community. In terms of responsiveness, it can be seen that the quality of human resources is minimum. On the other hand, the labor-intensive programs are not well implemented. Therefore, in carrying out its duties as a public servant, the village government must pay attention to and implement the concept of good governance properly, so that the implementation of the concept of good governance through optimizing the dimensions of transparency, accountability and responsiveness will encourage the realization of public trust in the village government, especially in the management of village funds.